2004
DOI: 10.1111/j.1365-2257.2004.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of seromarkers of HBV and HCV among blood donors in eastern Saudi Arabia, 1998-2001

Abstract: The prevalence of serological markers of HBV and HCV were determined for blood donors in eastern Saudi Arabia. Between 1998 and 2001, 13,443 donors (10,778 Saudi and 2665 non-Saudi), were screened for HBsAg, anti-HBc Ab, and anti-HCV Ab using commercial kits. There was a steady decrease in the HBsAg (2.58 and 1.67%), anti-HBc rates (15.32 and 9.15%), and anti-HCV (1.04 and 0.59%) rates between 1998 and 2001, respectively. However, there was a marked difference between Saudi and non-Saudi donors with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 15 publications
3
43
1
Order By: Relevance
“…This study presented that, the prevalence rate of HBs Ag was less than that has been previously reported in Sana'a City [13,14], In addition, the prevalence of HBs Ag in our study is quite similar to that reported by Acar et al [15], and Nazar et al [16] , whereas, slightly less than that reported by Al-Rubaye et al [17] , and Bashawri et al [18], who found that, (2.3%) and (2.58%) of blood donors have shown serological evidence for hepatitis B virus infection in Iraq and Saudi Arabia respectively.…”
Section: Discussionsupporting
confidence: 73%
“…This study presented that, the prevalence rate of HBs Ag was less than that has been previously reported in Sana'a City [13,14], In addition, the prevalence of HBs Ag in our study is quite similar to that reported by Acar et al [15], and Nazar et al [16] , whereas, slightly less than that reported by Al-Rubaye et al [17] , and Bashawri et al [18], who found that, (2.3%) and (2.58%) of blood donors have shown serological evidence for hepatitis B virus infection in Iraq and Saudi Arabia respectively.…”
Section: Discussionsupporting
confidence: 73%
“…The seroprevalence reported in previous Saudi studies showed marked variations by region and study population. The seroprevalence of HBV was high in Madinah (9.02%) [8] and the eastern region of Saudi Arabia (6.7%) [9]. In the south-western region, Najran city, the seroprevalence was much higher (8.7%) among health-care workers, while it was as low as 1.7% among health students [10].…”
Section: Discussionmentioning
confidence: 90%
“…Usually, HBV infection occurs when an individual receives blood with HBsAg and anti-HBc (Hepatitis B core antibody) in the serum or plasma of donors [25,26]. In Saudi Arabia, the prevalence of HBsAg in blood donors was found to range from 2.7% to 9.8% [9,11,12]. Also, the prevalence of anti-HBc and HBsAg negative blood samples was 3.2% [27] and 13.5% [9] in Saudi blood donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations